Impact of Concrete Grade and Stirrups Spacing on Performance Enhancement of Hybrid T-Beams Using Lightweight Concrete and High Compressive Strength Combinations - Ibrahim Idrees Ezzulddin; Hammad D. Merie (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
This study examines the performance of a total of ten reinforced concrete T-beams, nine of which were made as hybrid beams by casting the web with LW concrete and the flange with HS concrete; the last beam was cast as a normal beam (entirely cast with HS concrete). All beams underwent testing under two-point loads following a 28-day period. The variables of the experimental program include the concrete grade within the web (46, 62, and 82 MPa) and stirrup distribution distances (100, 200, and 300 mm). The experimental program includes load-deflection curves and failure modes for hybrid and normal beams. The results showed that all the beams failed in shear-flexural mode. Also, increasing flange compressive strength increased shear. strength. Increasing stirrup distribution distance from 100 to 200 and 300 mm reduced the ultimate load capacity; specimens with stirrup spacing of 300 mm failed directly after yielding of steel due to crushing the concrete over the support and spalling concrete cover within the shear zone. The study also determined that reducing stirrup spacing to 100 mm did not alter the failure mode, as shear failure was dictated by the compressive strength of the lower layer of the hybrid beams (19 MPa compressive strength of LW concrete).